Sestrin1, 2, and 3 are dispensable for female fertility in mice - Mengchen Wang; Wenhui Chen; Xinxin Zeng; Taojun Wang; Yingpu Sun; Qingling Yang (BMC, 2024)
Abstract Background Sestrins have been implicated in regulating aging in various organs through multiple pathways. However, their roles in ovarian aging remain unrevealed. Methods Female Sestrin1 −/− , Sestrin2 −/− , and Sestrin3 −/− mice were generated using the CRISPR-Cas9 system. Body weights, little sizes, ovarian weights, estrous cyclicity, and follicle number in female mice were observed. ELISA was utilized to measure serum anti-Müllerian hormone (AMH) levels. Real time PCR, western blot, immunofluorescence, and Masson trichrome staining were employed for assessment of aging-related change. Results The deletion of Sestrin 1, 2, or 3 had no discernible impact on body weights,or serum AMH levels in female mice at the age of 12 months. And there were no discernible differences in litter sizes or estrous cyclicity which were assessed at the age of 8 months. At the age of 12 months, no significant differences were observed in ovarian weights or follicle numbers among the knockout mice. Consistently, the extent of fibrosis within the ovaries remained comparable across all experimental groups at this age. Additionally, autophagy, apoptosis, DNA damage, and inflammation within the ovaries were also found to be comparable to those in wild-type mice of the same age. Conclusions The loss of Sestrin 1, 2, or 3 does not exert a noticeable influence on ovarian function during the aging process. Sestrin1, 2, and 3 are not essential for female fertility in mice.